Surfeit folic acid, protein, and exercise modify oncogenic inflammatory biomarkers and fecal microbiota - Tuska, Rebecca M.; Helm, Sophia M.; Graf, C. Foster; James, Courtney; Kong, Gabriel; Stiemsma, Leah T.; Green, David B.; Helm, Susan Edgar (Frontiers in Nutrition, 2023)
Intestinal microbiota, diet, and physical activity are inextricably linked to inflammation occurring in the presence of tumor progression and declining neurocognition. This study aimed to explore how fecal microbiota, inflammatory biomarkers, and neurocognitive behavior are influenced by voluntary exercise and surplus dietary protein and folic acid which are common health choices. Dietary treatments provided over 8 weeks to C57BL/CJ male mice (N=76) were: Folic Acid (FA) Protein (P) Control (FPC, 17.9% P; 2mgFA/kg); Folic Acid Deficient (FAD); Folic Acid Supplemented (FAS; 8mgFA/kg); Low Protein Diet (LPD, 6% P); and High Protein Diet (HPD, 48% P). FAS mice had decreased plasma HCys (p<0.05), therefore confirming consumption of FA. Objectives included examining influence of exercise using Voluntary Wheel Running (VWR) upon fecal microbiota, inflammatory biomarkers C-Reactive Protein (CRP), Vascular Endothelial Growth Factor (VEGF), Interleukin-6 (IL-6), nuclear factor kappa ß subunit (NF-𝜅ßp65), Caspase-3 (CASP3), Tumor Necrosis Factor-alpha (TNF-𝛼), and neurocognitive behavior. CRP remained stable, while a significant exercise and dietary effect was notable with increased VEGF (p < 0.05) and CASP3 (p < 0.05) for exercised HPD mice. Consumption of FAS did significantly decrease (p<0.05) muscle TNF-𝛼 and the ability to build a nest (p < 0.05) was significantly decreased for both FAD and LPD exercised mice. Rearing behavior was significantly increased (p<0.05) in mice fed HPD. Week 1, both weighted and unweighted UniFrac principal coordinates analysis yielded significant clustering (permanova, p ≤ 0.05) associated with the specific diets. Consumption of a HPD diet resulted in the most distinct fecal microbiota composition. At the phylum level–comparing week 1 to week 8– we report a general increase in the Firmicutes/Bacteroidetes ratio, characterized by an outgrowth of Firmicutes by week 8 in all groups except the HPD. MaAsLin2 analysis corroborates this finding and emphasizes an apparent inversion of the microbiome composition at week 8 after HPD. Explicit modification of oncogenic inflammatory biomarkers and fecal microbiome post high FA and protein intake along with voluntary exercise contributed to current underlying evidence that this diet and exercise relationship has broader effects on human health and disease–perhaps importantly as a practical modulation of cancer progression and declining neurocognition.